Learning Style of Students Who Become Athletes in Kupang - Christina Ikawany Riwu Manoe; Yeni Damayanti; Diana Aipipidely (Journal of Health and Behavioral Science, 2022)
Each student has the characteristics of a different learning style as well as an athlete. Learning styles are divided into three parts, namely visual learning styles, auditory learning styles, and kinesthetic learning styles. The purpose of this study is to describe the description of the learning styles of students who become athletes in the city of Kupang. This research is a qualitative research with descriptive method. The participants in this study were four student athletes who were selected using a purposive sampling method with the characteristics of being active in college and still attending training. The results showed that the four participants had different characteristics, namely two student athletes were more dominant in the visual learning style, while the other two student athletes were more dominant in the auditory and kinesthetic learning styles.